Pressure induced metastable polymerization in doped C60 materials. (May 2017) - Cui, Wen; Sun, Shishuai; Sundqvist, Bertil; Wang, Shuangming; Liu, Bingbing
Abstract: High pressure Raman studies have been carried out on C60 /AgNO3 and C60 /Ni(OEP) up to 30 GPa. In both these doped C60 materials, pressure-induced metastable ordered polymers can be observed after pressure release. The results show that both the quenched materials contain chainlike polymers and dimers. We also find that the degree of polymerization is higher in these doped C60 materials than in bulk C60 materials after similar high pressure treatment and that C60 /AgNO3 contains a higher fraction of chainlike polymers than C60 /Ni(OEP) after decompression from same pressure. The results can be understood by considering the different initial lattice structures of these materials and the confinement effects of the dopants. Graphical abstract: